Hydrocarbon prices and subsidies in Bolivia 1986-2025 - S. Mauricio Medinaceli Monrroy; Marcelo G. Velázquez Bilbao La Vieja (Institute for Advanced Development Studies (INESAD), 2023)
The following study identifies five periods with different price regimes (for main hydrocarbons): 1) 1986-1996, where these prices are part of the Government's fiscal policy to finance part of the structural adjustment policies after the inflationary period; 2) 19971999, when a new methodology for price determination based on three central components is implemented, international reference prices, transport, refining and sale margins and direct, indirect and consumption-specific taxes; 3) 2000-2003, period of privatization of refineries, transport and storage, where policies of stabilization of fuel prices took on greater relevance within the regulatory framework, an aspect that allowed to keep almost unchanged the final prices of gasoline and diesel, but with a considerable fiscal cost due to adjustment of the Special Tax on Hydrocarbons and their Derivatives (IEHD); 4) 2004-2005, where in 2004 a price band was determined for international reference price behavior; in this sense, international prices above USD/barrel 27.11 are not transferred to end consumers; and 5) 2005-2022, because in 2005 the last price adjustment was made (with the 2010 temporary increase exception) for gasoline, diesel oil and liquefied petroleum gas (LPG), which remained in force until 2022. Regarding the quantification of subsidies for production and consumption of hydrocarbons in Bolivia, five broad categories were considered in this document: an opportunity cost of selling production to the domestic market instead of its export; a direct import of petrol, diesel and LPG at higher prices for subsequent sale at lower prices; a non-updating of margins from the value chain of petroleum products; a fiscal sacrifice for non-collected VAT (Value Added Tax 13%) and; an incentive given to field operators in Bolivia. In total, it is estimated that by 2022 these five categories will represent 11.6% of gross domestic product (GDP), with the following disaggregation: opportunity cost (5.8%), direct import (3.1%), margin update (1.2%), tax sacrifice - VAT (1.1%), and incentive (0.4%).
Keywords: E62; E64; H21; L71; 330; Hydrocarbon prices; fiscal policy; taxes; subsidies